STRATEGI PENGEMBANGAN WISATA DI DUKUH BETUNG KABUPATEN KATINGAN - Tifani Novalita; Revi Sunaryati; Akhmat Sajarwan (Universitas Lambung Mangkurat, 2019)
Tourism is a natural resources utilization with low environmental impact. Tourism development and sustainability must be reciprocal. This research is aim to (1) inventory the tourism potential at Betung, (2) Analyze the Land Suitability and (3) design management strategy that can support the existence of Tourism at Dukuh Betung. This research is a survey research with in-depth interview techniques, field observations, and documentation. Data analysis techniques used are (1) Qualitative Descriptive, (2) Scoring, (3) SWOT. The results show that tourism potential at Betung includes the potential of natural resources, cultural, education, and human resources. Meanwhile, on observations of the Land Suitability shows that this area is feasible to be developed as a natural tourism area with the high scoring result (80). On SWOT Analysis, major internal factor for strength is natural and beautiful panorama and major internal factor for weaknesses is lack of human resources with appropriate competency. The major external factor for opportunity is this area can be treated as natural tourism, conservation, and education area. Meanwhile, major external factor for threats is the existence of other tourism attractions. Concluded based on the result study is :(1) Dukuh Betung area has various kinds of potential; (2) Land Suitability analysis shows that Dukuh Betung suitable to be developed as a natural tourism; (3 )On SWOT analysis, management strategy design that suitable to Dukuh Betung is WO (Weakness-Opportunity), strategy that fixed the weakness with improve the quality of human resources, improve and develop supporting facilities increasing community participation and increase in financial aspect.